EDUCACIÓN EN DERECHOS HUMANOS, TEORÍA CRÍTICA Y POLÍTICAS PÚBLICAS, ELEMENTOS PARA UNA REFLEXIÓN (2016)
The Current article aims to generate a reflection on how the human rights education must be connected to the critical thought. Likewise, it is guided on the critical theory and this relation with the public politics. This article is carried out using a qualitative research and the critical theory aims to the readers do a deep analysis about the importance of the human rights education in the Colombian Society nowadays.